2020
DOI: 10.1111/1753-0407.13082
|View full text |Cite
|
Sign up to set email alerts
|

Association between secondhand smoke exposure and diabetes mellitus in 131 724 Korean never smokers using self‐reported questionnaires and cotinine levels: Gender differences

Abstract: The aim of this study is to compare the gender-different associations between secondhand smoke (SHS) exposure and diabetes in self-reported never smokers verified by cotinine. Methods: Self-reported never smokers verified by cotinine levels (<50 ng/mL) enrolled in the Kangbuk Samsung Health Study between April 2011 and December 2016 were included for this study. SHS exposure was defined as current exposure to passive smoke indoors at home or workplace. The genderspecific association between SHS exposure and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The majority of the studies used a case-control design (n = 235), followed by prospective cohort (n = 156), nested case-control (n = 10), retrospective cohort (n = 5), case-cohort (n = 3) and case-crossover (n = 1) designs. The BPRF analyses for asthma (n = 125) and lung cancer (n = 104) reported in the present study were based on evidence from the highest number of studies, while COPD (n = 21) 48,177,208,225,236,[249][250][251][252][253][254][255][256][257][258][259][260][261][262][263][264] and type 2 diabetes (n = 9) [265][266][267][268][269][270][271][272][273] analyses were based on the lowest number of studies. The included studies represent 623 observations from over a priority for tobacco control efforts, especially after the adoption of the World Health Organization's Framework Convention on Tobacco Control, a global treaty aimed at implementing evidence-based measures to reduce both active and passive smoking 7 .…”
Section: Overviewmentioning
confidence: 99%
“…The majority of the studies used a case-control design (n = 235), followed by prospective cohort (n = 156), nested case-control (n = 10), retrospective cohort (n = 5), case-cohort (n = 3) and case-crossover (n = 1) designs. The BPRF analyses for asthma (n = 125) and lung cancer (n = 104) reported in the present study were based on evidence from the highest number of studies, while COPD (n = 21) 48,177,208,225,236,[249][250][251][252][253][254][255][256][257][258][259][260][261][262][263][264] and type 2 diabetes (n = 9) [265][266][267][268][269][270][271][272][273] analyses were based on the lowest number of studies. The included studies represent 623 observations from over a priority for tobacco control efforts, especially after the adoption of the World Health Organization's Framework Convention on Tobacco Control, a global treaty aimed at implementing evidence-based measures to reduce both active and passive smoking 7 .…”
Section: Overviewmentioning
confidence: 99%
“…Also, compared to men, the T2D burden attributable to secondhand smoke in women was higher and secondhand smoke was the main contributor to womens' tobacco-attributable T2D burden. Probably because daily time, frequency, and total duration of secondhand smoke exposure were higher in women, although secondhand smoke exposure prevalence was lower in women (46). Moreover, a prospective cohort in the US found a 16% higher rate of T2D among female nonsmokers with secondhand smoke exposure than those without (48).…”
Section: Discussionmentioning
confidence: 99%
“…Secondhand smoke, such as sidestream smoke, is mostly unfiltered and more likely to occur indoors at work or home, and its toxicity increases as it remains in the air for minutes or hours (45). Previous prospective studies have suggested the association between secondhand smoke and T2D risk (46,47). Also, compared to men, the T2D burden attributable to secondhand smoke in women was higher and secondhand smoke was the main contributor to womens' tobacco-attributable T2D burden.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influences of score in diet, smoke, and blood lipids on fragility fractures were not ascertain in this study, previous studies showed that both diet and lipid level are associated with sleep health and diabetes. [30][31][32] Therefore, considering the possible synergistic effect between the health-related behavioral elements, the CVH score including eight elements comprehensively may have better predictive value for fracture. In this context, the primary prevention of fragility fractures is more likely to be achieved by developing appropriate combined intervention strategies.…”
Section: Discussionmentioning
confidence: 99%